UNPACKING NIGERIA’S PEACE EFFORTS DURING THE SECOND CYCLE OF THE LIBERIAN CONFLICT - Oshewolo, Segun (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
Although peace operations have been a major instrument of Nigeria’s foreign policy continentally and globally, this study analyzed the country’s peace campaigns in Liberia under president Olusegun Obasanjo. The paper observed inter alia that Obasanjo’s peace efforts in Liberia were influenced by his recognition of Nigeria as a leading actor in the stabilization efforts in the region. While there were some encumbrances, Nigeria’s peace campaigns in Liberia were successful as revealed by the data sources. Nigeria’s major accomplishments included the eventual signing of a comprehensive peace agreement in 2003 that brought an end to the carnage in the country, offer of asylum to Taylor, and the 2005 post-conflict elections. These accomplishments could be attributed to President Obasanjo’s gravitas and Nigeria’s well-oiled diplomatic machinery in the West African sub-region. To arrive at this conclusion, the paper adopted the secondary data sources and interview technique for the purpose of data collection, and descriptive thematic analysis.